The Effectiveness of Hopeful Mind Program among Primary School Children in Malaysia: A Preliminary Study - Ghazali, S.R; Chen, Yoke Yong; C., Basco; K., Kirby; C., Armour; K., Goetzke; M., Dunne; W., Gibbons; P., McFadden; J., Mallet; A., Rodgers (Universal Publishers, 2021)
The increasing prevalence of mental disorders among children warrant an investigation to evaluate the effectiveness of mental health prevention program to help children dealing with life challenges effectively. A quasi-experimental pre prevention-post prevention research design was conducted to evaluate the effectiveness of Hopeful Mind program among primary school children in Malaysia. Sixty-nine primary school children aged 10-11 participated in this study. Thirty-seven of them were randomly assigned in prevention group and 32 of them were assigned in control group. Results showed that the depressive symptoms for the prevention groups decreased significantly. The prevention group showed a significant improvement in their negative emotional regulation and in controlling their emotions. Results also showed some significant findings between genders. Male children reported significant decreased score in depression and gained significant score improvements in emotional control than the female. Thus, the present study suggested that Hopeful Mind program is feasible in supporting Malaysia children in terms of reducing their depressive symptoms, regulating and controlling their emotion. Several limitations and recommendation for future studies were discussed and presented